2022
DOI: 10.3389/fcimb.2022.1073113
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota signature as predictors of adverse outcomes after acute ischemic stroke in patients with hyperlipidemia

Abstract: IntroductionThe alterations of gut microbiota have been associated with multiple diseases. However, the relationship between gut microbiota and adverse outcomes of hyperlipidemic stroke patients remains unclear. Here we determined the gut microbial signature to predict the poor outcome of acute ischemic stroke (AIS) with hyperlipidemia (POAH).MethodsFecal samples from hyperlipidemic stroke patients were collected, which further analyzed by 16s rRNA gene sequencing. The diversity, community composition and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…At present, there are some studies focusing on the gut microbiota of AIS or specific AIS populations, such as the study reported by Chen et al. ( Chen et al., 2022 ). Chen’s study was to investigate the characteristic gut microbiota of poor outcome of AIS with hyperlipidemia (POAH) patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are some studies focusing on the gut microbiota of AIS or specific AIS populations, such as the study reported by Chen et al. ( Chen et al., 2022 ). Chen’s study was to investigate the characteristic gut microbiota of poor outcome of AIS with hyperlipidemia (POAH) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Stool samples (200 mg) were collected and stored in the Fecal Microbial Collection and Preservation Kit (ML-001A, Shenzhen Dayun Gene Technology Co., Ltd.) and saved in an -80°C refrigerator within 3 days ( Chen et al., 2022 ; Luo et al., 2022 ). Total DNA was extracted following the manufacturer’s instructions using CTAB method.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported that GM composition influences stroke prognosis ( 57 , 58 ). The GBA regulates immunological functions in the post-stroke condition while altered GM composition and abundance affect post-stroke outcomes mainly via gut leakiness, endotoxemia, and the neuroimmune axis.…”
Section: Evidence Of Gut Dysbiosis In Neurological Disordersmentioning
confidence: 99%
“…These findings demonstrate that GM might be an important regulator of the prognosis of hyperlipidaemic stroke and its consequences. In this sense, a recent study demonstrated that the GM signature of hyperlipidaemic patients is a predictor of adverse outcomes after acute ischaemic stroke, as determined by modified Rankin Scale (mRS) scores at 3 months after admission (Chen, Chi, et al, 2022). Hypertension is the most prevalent modifiable risk factor for stroke and dementia (van der Flier et al, 2018).…”
Section: The Microbiota–gut–brain Axis In the Acute And Chronic Strok...mentioning
confidence: 99%